Elastic Guided Waves in Bistable Composite Structures - Experimental and Numerical Investigation - Saad, D.M.; Mustapha, S.; Firouzian-Nejad, A.; Aziz, A. Abdul (Current Mechanics and Advanced Materials (Discontinued), 2022)
Background: Bistable composite laminates are emerging as smart structures in automotive and aerospace applications. However, the behavior of the wave propagation within such laminates has not been investigated, which hinders their implementation in Structural Health Monitoring (SHM) and Non-Destructive Evaluation (NDE). Objective: As a result, this manuscript examines the propagation behavior of guided waves in bistable composite structures. By understanding the effect of pre-stressing in bistable composite laminates on the characteristics of propagating waves, such as velocity and amplitude, a more knowledgeable decision about their applications in flaw detection and assessment can be made. Methods: The fundamental symmetric (S0) and anti-symmetric (A0) Lamb wave modes were investigated during propagation in two bistable composite laminates, [0/90]T and [02/902]T, and were assessed experimentally and numerically using ABAQUS. For the tested frequencies, which ranged from 60 kHz to 250 kHz, the behavior of the propagating wave was evaluated for both stable configurations and across two different actuators that were lined up with the fiber directions. Signal processing techniques were thus extensively used to enhance the measured signals and identify both the group velocities and the amplitudes’ trend of the S0 and A0 wave modes. Results: Our results showed that there is a minimal variation (typically below 1%) in the amplitude and velocity of the A0 and S0 modes when the composite plates switch between the first stable configuration and the second stable configuration in both composite plates. These results were numerically validated by replicating the bi-stability of the composites. The numerical data were in relatively close agreement (10% average error) with the experimental values and trends. Furthermore, the bistable effect was examined in detail relative to a reference numerical flat (monostable) plate. Although the bistable effect induced a notable amount of internal residual stress, this did not significantly impact the propagating wave modes, with a maximum difference of about 2% when comparing wave velocities. Conclusion: The effect on the wave propagation behavior along different directions of both stable configurations was shown to be minimal. These results, which were validated numerically, clear the ambiguity on the usage of these laminates in experimental health monitoring.
Keywords: finite element analysis